New challenges, new tools for defense decisionmaking - Johnson, Stuart E., 1944-; Libicki, Martin C.; Treverton, Gregory F.; Bennett, Bruce W., 1952-; Berstein, Nurith, 1968-; Camm, Frank A., 1949-; Chu, David S. C.; Davis, Paul K., 1943-; Fox, Daniel B. (Daniel Bryan), 1946-; Hosek, James R.; Mussington, David, 1960-; Starr, Stuart H.; et al. (Santa Monica, CA : RAND, 2003)
It is still easy to underestimate how much the collapse of the Soviet Union and the end of the Cold War and then the terrorist attacks of September 11, 2001 transformed the task of American foreign and defense policymaking. In place of predictability (if a sometimes terrifying predictability), the world is now very unpredictable. In place of a single overriding threat and benchmark by which all else could be measured, a number of possible threats have arisen, not all of them states. In place of force-on-force engagements, U.S. defense planners have to assume "asymmetric" threats ways not to defeat U.S. power but to render it irrelevant. This book frames the challenges for defense policy that the transformed world engenders, and it sketches new tools for dealing with those challenges from new techniques in modeling and gaming, to planning based on capabilities rather than threats, to personnel planning and making use of "best practices" from the private sector.
Introduction -- Introduction to Part I: New Challenges for Defense -- Decisionmaking for Defense -- Responding to Asymmetric Threats -- What Information Architecture for Defense? -- Introduction to Part II: Coping with Uncertainty -- Incorporating Information Technology in Defense Planning -- Uncertainty-Sensitive Planning -- Planning the Future Military Workforce -- The Soldier of the 21st Century -- Adapting Best Commercial Practices to Defense -- Introduction to Part III: New Tools for Defense Decisionmaking -- Exploratory Analysis and Implications for Modeling -- Using Exploratory Modeling -- Assessing Military Information Systems -- The "Day After" Methodology and National Security Analysis -- Using Electronic Meeting Systems to Aid Defense Decisions.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: National security -- United States; World politics -- 21st century; United States -- Defenses; United States -- Military policy -- Decision making